2015
DOI: 10.1111/1348-0421.12210
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive oral administration of Bifidobacterium longum MM‐2 improves the defense system against influenza virus infection by enhancing natural killer cell activity in a murine model

Abstract: Bifidobacterium, one of the major components of intestinal microflora, shows anti-influenza virus (IFV) potential as a probiotic, partly through enhancement of innate immunity by modulation of the intestinal immune system. Bifidobacterium longum MM-2 (MM-2), a very safe bacterium in humans, was isolated from healthy humans and its protective effect against IFV infection in a murine model shown. In mice that were intranasally inoculated with IFV, oral administration of MM-2 for 17 consecutive days improved clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 51 publications
3
69
0
1
Order By: Relevance
“…Gene expression profiling of these DCs revealed evidence for a modest pre-activation of DCs when Bifidobacterium was present, arguing for an innate immune mechanism for this improved immune activation effect [90]. This observation is similar to what has been reported in a viral infection model, in which gut bacteria induced APC "poising" [91]. In agreement, germ-free or antibiotic-treated mice, which completely lack or have a compromised commensal microbiota, showed defective innate immunity during viral infection [92,93].…”
Section: Functional Interaction With the Commensal Microbiotasupporting
confidence: 78%
“…Gene expression profiling of these DCs revealed evidence for a modest pre-activation of DCs when Bifidobacterium was present, arguing for an innate immune mechanism for this improved immune activation effect [90]. This observation is similar to what has been reported in a viral infection model, in which gut bacteria induced APC "poising" [91]. In agreement, germ-free or antibiotic-treated mice, which completely lack or have a compromised commensal microbiota, showed defective innate immunity during viral infection [92,93].…”
Section: Functional Interaction With the Commensal Microbiotasupporting
confidence: 78%
“…Recently, we showed that changes in the composition of the gut microbiota towards a dysbiotic condition resulted in higher oropharyngeal and cloacal shedding of AIV subtype H9N2 in chickens, which was also associated with compromised type I interferon (IFN) expression 19 . However, altering the composition of gut microbiota using probiotics has shown beneficial effects on immunity to influenza virus infection 20,21 . For instance, oral administration of a human isolate of Bifidobacterium longum MM-2 to influenza-infected mice reduced influenza virus associated mortality and inflammatory responses in the lower respiratory tract 20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, altering the composition of gut microbiota using probiotics has shown beneficial effects on immunity to influenza virus infection 20,21 . For instance, oral administration of a human isolate of Bifidobacterium longum MM-2 to influenza-infected mice reduced influenza virus associated mortality and inflammatory responses in the lower respiratory tract 20 . The major mechanisms involved were shown to be the activation of natural killer (NK) cells both in the lungs and spleen and increased expression of various cytokines in the lungs 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kawahara et al [65] reported that supplementation with B. longum MM-2 was linked to increases in natural killer (NK) cell activity, potentially via an increase in NK cell-activating cytokines such as IL-18, and correlated with anti-influenza virus responses. In an obesity-associated inflammation model, B. pseudocatenulatum CECT 7765 reduced B-cell (CD19 + ) and pro-inflammatory macrophages (F4/80 + CD11c − CD206 + ), as well as increasing Treg responses, which correlated with reduced body weight gain and improved glucose tolerance [66].…”
Section: Other Cells Typesmentioning
confidence: 99%